A Two-Step SO3H/ICG Catalyst Synthesis for Biodiesel Production: Optimization of Sulfonation Step via Microwave Irradiation - Nur Nazlina Saimon; Norzita Ngadi; Mazura Jusoh; Zaki Yamani Zakaria (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Conventional heating, a common method used for heterogeneous solid acid catalyst synthesis unknowingly consumes massive time and energy. In this study, acid catalyst was prepared through sulfonation process of incomplete carbonized glucose (ICG) via microwave-assisted technique to shorten the heating time and energy consumption. Optimization of the sulfonation process of ICG via microwave-assisted was carried out. Four-factor-three-level central composite design (CCD) was used to develop the design of experiments (DOE). Interaction between two factors was evaluated to determine the optimum process conditions. A quadratic model was proposed for prediction of biodiesel yield (Y) from palm fatty acid distillate (PFAD) and its conversion (C). The application of DOE successfully optimized the operating conditions for the two-step SO3H/ICG catalyst synthesis to be used for the esterification process. The optimized conditions of the best performing SO3H/ICG with maximum Y and C were at 7.5 minutes of reaction time, 159.5 mL of H2SO4 used, 671 rpm of stirring rate as well as 413.64 watt of power level. At these optimum conditions the predicted yield percentage and conversion percentage were 94.01% and 91.89%, respectively, which experimentally verified the accuracy of the model. The utilization of sulfonated glucose solid acid catalyst via microwave-assisted in biodiesel production has great potential towards sustainable and green method of synthesizing catalyst for biodiesel. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).